E. Hoyt orderly book and narrative sketchbook - Hoyt, E. (Epaphras), 1765-1850.
Orderly book and narrative sketchbook bound together in one volume. Orderly book (1814-1819) contains military orders, camp duty listings, militia records, and rosters for the 2nd brigade, 4th division, Massachusetts militia; and narrative sketchbook (1839-1840) contains Hoyt's comments on topics including Northern and Southern views on slavery and abolition.
Surveyor, author, historian, and militia officer of Deerfield, Franklin County, Mass.
Collection material in English.
Keywords: Antislavery movements; Slavery; Deerfield (Mass.) -- History; Franklin County (Mass.) -- History; Massachusetts -- History -- 1775-1865.; Massachusetts -- Militia; Authors; Historians; Militia officers; Surveyors